Ostracodes do cretáceo-paleógeno inferior da Bacia de Pelotas - Ceolin, Daiane (Universidade do Vale do Rio dos Sinos, 2010)
The taxonomic study of marine ostracods from Pelotas Basin and the respectives paleoecological assemblages aspects in the Cretaceous and Cretaceous – Lower Paleogene interval were studied. 479 cutting samples from wells 1-RSS-2, 1-RSS-3, 2-RSS-1, 1-SCS-3B e 1-SCS-2 were analized. 98 specimes belonging to 9 families, 21 genera and 34 species. 2 genera and 2 species were supported as undetermined taxon. The species identified were: Cytherella cf. C. araucana Bertels, 1974; Cytherelloidea spirocostata Bertels, 1973; Bairdoppilata triangulata Edwards, 1944; Actinocythereis indígena Bertels, 1969; Brachycythere gr. sapucariensis Krömmelbein, 1964; ichmannella araucana Bertels, 1969 and Wichmannella meridionalis Bertels, 1969. The most diversified genera were Cytherella and Paracypris with 7 and 4 species, respectively. The Turonian was the most ostracodes-rich interval with significant presence of the genera Brachycythere and Cytherella. The most abundant families were Trachyleberididae and Cyther ellidae with 2 genera and 8 species. The K – Pg boundary in the Pelotas basin is marked by a faunal change which disappearance the genera Cytherelloidea, Argilloecia, Cythereis, Brachycythere, Pondoina and Rostrocytheridea, and the first occurrence of Neonesidea, Bairdoppilata, Ambocythere Buntonia, Langiella?, Trachyleberis and Krithe. The Cretaceous ostracods association in Pelotas Basin sugest a neritic marin e environment with warm water temperatures.
Keywords: Bacia de Pelotas; Ostracodes; Cretáceo; Paleógeno; Pelotas Basin; Ostracods; Cretaceous; Paleogene; ACCNPQ::Ciências Exatas e da Terra::Geologia